A promising way to detect and fight different types of tumors and cancer by using nuclear science and magnetic carbon - M. Araujo-Moreira, Fernando; Cavaliere de Medeiros, Marcos Paulo (Revista Brasileira de Saúde Militar, 2023)
In this review of our own work, we show a promising way to detect and fight different types of tumors and cancer by using nuclear science and magnetic carbon. Almost two decades ago, we reported by the first time on a chemical route aiming to synthetize stable magnetic carbon/graphite. By using the Nuclear Magnetic Resonance (NMR) technique we have verified that its magnetism is an intrinsic property of this synthetized material and not originated from ferromagnetic impurities of any kind. Through direct measurement of the local magnetic field using Carbon-13 we have concluded that its magnetism is originated from defects in the structure. From its biocompatibility, we have been working in the use of magnetic carbon/graphite to deliver many compounds aiming to fight different diseases. Despite all scientific and technological advances of present days, cancer is a multifactorial and difficult to treat disease, killing hundreds of thousands of people a year worldwide. Therefore, the development of a new and efficient drug delivery system to fight cancer and biological agents – among other diseases - is as important as the discovery of a novel active molecule. In this work, we show the drug delivery system named MAGUS® (an acronym for Magnetic Graphite Universal System) we have built based on nanostructured magnetic carbon/graphite. This is an innovative and promising system composed by a biocompatible nanostructured particle of magnetic carbon/graphite functionalized with different molecules and materials. MAGUS®, depending on what we link to its structure, is so versatile and can be used to detect a wide range of specimens, from tumors and cancers to chemical and biological agents used as non-conventional weapons. That is why we call it universal. In the present work, MAGUS® will be acting as a biosensor, where the magnetic carbon/graphite is functionalized with radioactive particles of Iodine-131 and antibodies of different types of cancer. Then, by focusing on both the antigen-antibody interaction and the spatial guiding through an external magnetic field we are providing our drug delivery system a double way to detect and reach just the target. Based on these strategies, the functionalized magnetic carbon/graphite will reach only the neoplasm and not the surrounding healthy cells around. In a general view, it means that we are giving specificity to the MAGUS® drug delivery system as a pioneering and effective way to detect and treat cancers. We are also working on this unprecedented and efficient drug delivery system using the principles of Boron Neutron Capture Therapy (BNCT) with Boron-10 instead of Iodine-131. BNCT technique uses neutron as the external source and is frequently employed to treat specific tumors that are radioresistant or very difficult to kill using conventional radiation therapy. In summary, we show here by the first time that our Magnetic Graphite Universal System associated with nuclear techniques can be successfully used as a biosensor to detect and fight cancers and tumors with powerful features that conventional delivery drugs systems and other treatments do not have at all.